Historical appraisal analysis: evaluation of the book in sixteenth-century England - Ruokkeinen, Sirkku (fi=Turun yliopisto|en=University of Turku|, 2021)
This dissertation is a study of the evaluation of the book in the English Renaissance. The purpose of the study is to find out what a good book was like in sixteenth-century England, what personal and societal attitudes were held towards books and literature, and how these attitudes were expressed linguistically. While some of these attitudes have been studied previously, the focus has been limited according to genre. The anxieties related to translating ancient classics and the necessity of vernacularizing medical texts have received some attention. Yet, no previous linguistic analyses of these attitudes have been conducted, and linguistic analyses of evaluative language in general have been rare in historical materials. The material for this study consists of a self-built 70,000-word corpus of English Renaissance translator’s paratexts. The corpus consists of 30 dedications and 41 prefaces, collected from the full range of available topics and genres. I analyze the evaluative language within the corpus texts using the Appraisal Framework, a discourse semantic tool for the categorization and analysis of evaluative language. This study shows that the early modern English book was appraised largely for its internal and external value: the distinction it has among others of its type and its usefulness to its reader. The original author of the work is subjected to succinct positive appraisals of their character, while the translator is appraised with more complex structures expressing both positive and negative attitudes related to their capacity and tenacity. The topic of the main text has a heavy influence on the appraisals. While the paratexts to classical translations focus on negative appraisals following textual conventions, the paratexts to more utilitarian texts opt for more positively toned appraisal profiles. Medical texts are presented more positively, and geographical and navigational works circumvent the traditional positive author appraisal to benefit other targets. In addition to advancing the understanding of early modern English book culture, this study contributes to the knowledge of evaluative language as a discourse semantic phenomenon, and expands its study to earlier historical periods.

Tämä tutkielma käsittelee arvottavaa kieltä ja kirjoihin kohdistuvia asenteita 1500-luvun Englannissa. Tutkimuksen tavoitteena on selvittää, millaisia kirjoja arvostettiin renessanssiajan Englannissa, millaisia asenteita kirjoihin kohdistui, ja miten näitä asenteita ilmaistiin kielellisin keinoin. Jotkut varhaismodernin Englannin kirjoihin kohdistuvista asenteista tunnetaan varsin hyvin. Erityisesti antiikin kreikkalaisten ja roomalaisten tekstien sekä retoriikan vaikutus kirjoihin liittyvään diskurssiin on varsin hyvin tunnettu. Samoin lääketieteellisten tekstien kääntämiseen kohdistuvia asenteita on tutkittu viime vuosina. Nämä tutkimukset eivät kuitenkaan ole kielitieteellisiä tai keskity arvottavaan kieleen. Kielitieteellinen tutkimus arvottavasta kielestä historiallisissa konteksteissa on ylipäätään vielä varsin vähäistä. Tutkimuksen materiaalina toimii 70 000 sanan korpus englantilaisten kääntäjien parateksteistä. Korpus koostuu 30 omistuskirjoituksesta ja 41 esipuheesta. Korpuksen paratekstejä ei ole rajattu päätekstin genren tai aiheen mukaan, vaan niitä on koottu kaikista genreistä. Arvottavan kielen analyysi tapahtuu käyttäen Appraisal-teoriaa, joka on arvottavan kielen luokitteluun analyysiin kehitetty diskurssisemanttinen metodologia. Tutkimus osoittaa, että varhaismoderniin englantilaiseen kirjaan kohdistuvat arvotukset perustuivat pääsääntöisesti kirjan sisäiseen arvoon tai sen arvoon kontekstissaan: kirjan erikoislaatuisuuteen ja hyödyllisyyteen. Kirjoittajaa arvotettiin käyttäen yksinkertaista, positiivista kieltä, joka kohdistui tämän soveliaisuuteen, kun taas kääntäjää arvotettiin monimutkaisilla ilmauksilla, joilla kommunikoitiin samanaikaisesti positiivisia ja negatiivisia asenteita. Kääntäjän kompetenssi kiistetään, mutta tämän sitkeyttä kehutaan. Päätekstin sisältö vaikuttaa arvottavaan kieleen ja kirjaan kohdistuviin asenteisiin. Antiikin klassisten tekstien käännökset noudattavat nöyryysdiskurssia, kun taas käyttö- ja tietokirjallisuuden parateksteissä arvottava kieli on tyypillisesti positiivisempaa. Tutkimuksellani tuotan tietoa varhaismodernin englannin kielen kirjallisesta kulttuurista ja arvottavan kielen toimintamekanismeista sekä laajennan arvottavan kielen tutkimusta aiemmille aikakausille.